Photophysical and Biological Profiling of Ruthenium(II) Polypyridyl Complex-based Systems - ESTALAYO, SANDRA (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2019)
Ruthenium(II) polypyridyl complexes have been shown to be promising compounds for the design of novel metal-based therapeutic and imaging agents due to their attractive and tuneable photochemical, photophysical and redox properties. This thesis, entitled "Photophysical and Biological Profiling of Ruthenium(II) Polypyridyl Complex-based Systems", is focused on the development of new Ru(II) polypyridyl complexes with a view to exploiting their attractive photophysical properties for use in biological applications, specifically in the context of DNA binding and photodynamic therapy (PDT) for the treatment of cancer. The research work presented here is divided into seven chapters. Chapter 1, the introduction, first provides a brief overview of the current therapies used in the treatment of cancer. The sections that follow focus on discussing in more detail the two therapeutic strategies most pertinent to this thesis: DNA binding and PDT. Therefore, a description of the DNA structure is given, as well as the different binding modes by which molecules can interact with DNA. The mechanism of action of PDT is then described, and some examples of photosensitisers approved for clinical use in the treatment of cancer are also provided. Following this, the applicability of metal-based compounds as anticancer agents is discussed with particular emphasis on the potential of certain ruthenium complexes. A description of the photophysical properties of Ru(II) polypyridyl complexes and their application as DNA binding, cellular imaging, and PDT agents is also given and supported by relevant examples from the literature. The remainder of the chapter provides a brief account of the properties of gold nanoparticles (AuNPs) and their potential use as platforms for applications in biomedicine. This chapter concludes by reviewing recent examples of Ru(II)-based systems developed in the Gunnlaugsson group and also includes a description of the aims of the research work conducted in each of the subsequent chapters. In Chapter 2, the synthesis and photophysical evaluation of a series of Ru(II) polypyridyl complexes based on an extended aromatic ligand, dipyrido[3,2-a:2',3'-c][1,2,5]thiadiazolo[3,4-h]phenazine, or dtp, is presented. Their DNA binding properties are then evaluated using various spectroscopic techniques, such as UV-vis absorption and emission spectroscopy, DNA thermal denaturation, circular dichroism as well as viscosity measurements. In addition, their ability to produce singlet oxygen in DNA-free or -containing media is investigated, followed by their cellular uptake and phototoxicity against HeLa cervical cancer cells. Part of this chapter has been published in Dalton Transactions (2016, 45, 18208-18220). Chapter 3 describes a detailed spectroscopic study on the photoadduct formed by covalent binding between the pi-deficient complex [Ru(TAP)3]2+ (TAP = 1,4,5,8-tetraazaphenanthrene) and the guanine-containing nucleotide guanosine 5'-monophosphate (GMP) under irradiation with visible light. The pH effect on the spectroscopic properties of such a photoadduct on both ground and excited states is probed with a view to gain further insight into the elusive mechanism by which this mono-photoadduct is capable of reacting with a second molecule of GMP under further irradiation and form a bi-photoadduct, despite its non-emissive character. This double photoreactivity is of particular interest in irreversible and photocontrolled DNA damage via crosslinking of the two DNA strands. In Chapter 4, a family of water-soluble amphiphilic Ru(II) polypyridyl complexes is discussed. These complexes possess both a hydrophilic head-group (Ru(II) complex moiety) and different length hydrophobic tails (ten or twenty-one carbon alkyl chains). Ru(II) complexes containing only a methyl group and the parent complexes [Ru(phen)3]2+ and [Ru(TAP)2phen]2+ (phen = 1,10-phenanthroline) are also used for comparison. The formation of supramolecular micellar species from the complexes containing the longest alkyl chain is investigated with focus being paid towards determining the critical micelle concentration (cmc) and an estimation of their size. Moreover, the influence of the alkyl chain length in the photophysical properties, DNA binding and singlet oxygen generation is evaluated. Their alkyl chain length-dependent cellular internalisation and their ability to act as PDT agents in live cells is also examined. Chapter 5 details the synthesis and photophysical characterisation of a series of alkyl disulphide functionalised dinuclear Ru(II) polypyridyl complexes and the conjugates resulting from their attachment onto the surface of AuNPs. Their suitability for use in a cellular environment is also assessed by preliminary cellular uptake and phototoxicity studies. Finally, an overall conclusion of this work is presented in Chapter 6, while Chapter 7 outlines the experimental procedures, and presents the synthesis and characterisation of the compounds discussed within this thesis. Subsequently, literature references and the Appendices are provided, the latter containing supplementary experimental data to support the work described in the main text.
APPROVED
Keywords: Ruthenium(II) polypyridyl complexes; Spectroscopy; DNA binding; Light-switch effect; Luminescence quenching; Luminescent cellular probes; Photodynamic therapy; Singlet oxygen; Phototoxicity; Cellular uptake; Photo-induced electron transfer; DNA photoadducts; Photocrosslinking; Luminescent metallosurfactants; Critical micelle concentration; Lipophilicity; Gold nanoparticles; Drug delivery